PORTRAYING THE WORD “TOURISM” IN ENGLISH: A CORPUS LINGUISTIC STUDY - Eva Tuckyta Sari Sujatna; Heriyanto Heriyanto; Ekaning Krisnawati; Rosaria Mita Amalia; Kasno Pamungkas (Universitas Padjadjaran, 2020)
Now days, tourism is counted as a large industry that could support the government income. Since tourism is important, it is essential to promote it by online and offline media. Corpus of Contemporary American English (COCA) was claimed as a large corpus of language is the source of the data taken in this paper. Many researchers do their research on tourism, but it is limited research on the word tourism related to corpus. The aims of the research are, firstly, to describe the distribution of the word “tourism” in COCA since 1990 up to 2019 including across different contexts and secondly, to describe the pair of the word “tourism” in COCA since 1990 up to 2019 including its context. The research method implemented is a mixed method design, that quantitative and qualitative methods are combined. It was reported, firstly, from 9833 corpus containing the word “tourism” found in COCA, the highest number is newspaper followed by academy, magazine, spoken, web, fiction, blog, TV, and movie. Secondly, from the highest number to the smallest number of the subtypes of the word tourism are related to nature, culture, animal, place, sport, history, prostitution, health, religion, science, memory, crime, movie, and charity.